2011
DOI: 10.1038/nature09787
|View full text |Cite|
|
Sign up to set email alerts
|

Telomere dysfunction induces metabolic and mitochondrial compromise

Abstract: Telomere dysfunction activates p53-mediated cellular growth arrest, senescence and apoptosis to drive progressive atrophy and functional decline in high-turnover tissues. The broader adverse impact of telomere dysfunction across many tissues including more quiescent systems prompted transcriptomic network analyses to identify common mechanisms operative in haematopoietic stem cells, heart and liver. These unbiased studies revealed profound repression of peroxisome proliferator-activated receptor gamma, coactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
982
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,152 publications
(1,077 citation statements)
references
References 44 publications
45
982
9
1
Order By: Relevance
“…Interestingly, PGC‐1α levels are increased by exercise in muscle (Safdar et al., 2011) and PGC‐1α is considered to be a key player in mitochondrial changes induced by exercise (Safdar et al., 2011; Ventura‐Clapier, Mettauer, & Bigard, 2007). In addition, PGC‐1α extends health span and life span of a mouse model of premature aging arising from mitochondria defects (Sahin et al., 2011). Importantly, in line with the mitochondrial decline, PGC‐1α expression decreases during muscle aging in different species, including humans (Ghosh et al., 2011; Kang, Chung, Diffee, & Ji, 2013; Short et al., 2005; Vina et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PGC‐1α levels are increased by exercise in muscle (Safdar et al., 2011) and PGC‐1α is considered to be a key player in mitochondrial changes induced by exercise (Safdar et al., 2011; Ventura‐Clapier, Mettauer, & Bigard, 2007). In addition, PGC‐1α extends health span and life span of a mouse model of premature aging arising from mitochondria defects (Sahin et al., 2011). Importantly, in line with the mitochondrial decline, PGC‐1α expression decreases during muscle aging in different species, including humans (Ghosh et al., 2011; Kang, Chung, Diffee, & Ji, 2013; Short et al., 2005; Vina et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, late‐generation (G3 and beyond) TERT (Rudolph et al ., 1999) or TERC‐deficient mice (TERT −/− and TERC −/− , respectively) are short living and show reduced fertility, early alopecia, kyphosis, anemia, and lymphopenia (Wong et al ., 2003). Interestingly, TERC −/− mice present altered mitochondrial functions, including increased production of reactive oxygen species (ROS) from the electron transfer chain (ETC) (Passos et al ., 2010; Sahin et al ., 2011). Thereby, telomeres have been suggested to play a role in controlling mitochondrial ROS accumulation and oxidative stress during aging (Sahin & Depinho, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that treating mouse embryos with chemicals able to induce mitochondrial dysfunction and ROS accumulation, led to telomere loss and chromosomal instability, which was prevented by a concomitant treatment with N ‐acetylcysteine, a compound that improves ROS scavenging (Liu et al ., 2002). However, other mutations in genes involved in ROS metabolism, such as SOD2 haploinsufficiency, do not cooperate with telomere dysfunction (Guachalla et al ., 2009), and the treatment with N ‐acetylcysteine does not rescue progeric phenotypes of late‐generation TERT‐deficient mice (Sahin et al ., 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dr. Ron DePinho (MD Anderson/Dana Farber) proposed a new theory for aging based on his experiments with telomerase-deficient mice [73][74][75][76] ( Fig. 8).…”
Section: A New Theory For Aging That Connects Telomerase With Mitochomentioning
confidence: 99%